Luminescent biomimetic citrate-coated europium-doped carbonated apatite nanoparticles for use in bioimaging: physico-chemistry and cytocompatibility. Issue 5 (10th January 2018) - Gómez-Morales, Jaime; Verdugo-Escamilla, Cristóbal; Fernández-Penas, Raquel; Parra-Milla, Carmen María; Drouet, Christophe; Maube-Bosc, Françoise; Oltolina, Francesca; Prat, Maria; Fernández-Sánchez, Jorge Fernando
Abstract : Biomimetic citrate-coated europium doped carbonated apatite nanoparticles show a high luminescence intensity and cytocompatibility for uses in cell/tissue imaging. Abstract : Nanomedicine covers the application of nanotechnologies in medicine. Of particular interest is the setup of highly-cytocompatible nanoparticles for use as drug carriers and/or for medical imaging. In this context, luminescent nanoparticles are appealing nanodevices with great potential for imaging of tumor or other targetable cells, and several strategies are under investigation. Biomimetic apatite nanoparticles represent candidates of choice in nanomedicine due to their high intrinsic biocompatibility and to the highly accommodative properties of the apatite structure, allowing many ionic substitutions. In this work, the preparation of biomimetic (bone-like) citrate-coated carbonated apatite nanoparticles doped with europium ions is explored using the citrate-based thermal decomplexing approach. The technique allows the preparation of the single apatitic phase with nanosized dimensions only at Eu 3+ doping concentrations ≤0.01 M at some timepoints. The presence of the citrate coating on the particle surface (as found in bone nanoapatites) and Eu 3+ substituting Ca 2+ is beneficial for the preparation of stable suspensions at physiological pH, as witnessed by the ζ -potential versus pH characterizations. The sensitized luminescence features of the solid particles, as a function of the Eu 3+ doping concentrations and the maturation times, have been thoroughly investigated, while those of particles in suspensions have been investigated at different pHs, ionic strengths and temperatures. Their cytocompatibility is illustrated in vitro on two selected cell types, the GTL-16 human carcinoma cells and the m17.ASC murine mesenchymal stem cells. This contribution shows the potentiality of the thermal decomplexing method for the setup of luminescent biomimetic apatite nanoprobes with controlled features for use in bioimaging.